Important amendments to the family law in the bill to reform the civil and commercial codes of Argentina 2012 - Medina, Graciela (2013)
The Bill to unify the Civil and Commercial Code drafted by the commission appointed by Presidential Decree Nº 211 ofFebruary 23, 2011 contains majorreforms to Family Law, which we propase to list in this article. The most important ones are: changing traditional names. The explicit dwindling of personal responsibilities of marriage, including the weakening of the duties of fidelity and moral support. No1ault divorce. The regulation of cohabitation called domestic partnership. The establishment of responsibilities of step-parents. The acceptance of a third type of filiation. Filiation of a child born of assisted procreation. The possibility of prenuptial agreement. The establishment of a new, more complex, adoption procedure, with more actors and prevailing role of the administrative body. Family proceedings rules